Myanmar Government's Response to the Emergency Condition of Humanity and Health Crisis in the COVID-19 Pandemic - Putri, Ananda Ramadhani; Siregar, Roqsunnisa Dienda Arnauly; Avivi, Yusron (Universitas Sebelas Maret, 2020)
The humanitarian crisis in Myanmar is still ongoing today, especially humanitarian and health problems suffered by ethnic Rohingya. Myanmar government's lack of response in resolving this humanitarian crisis is already a concern to the whole world. The lack of existing health facilities for ethnic Rohingya especially during the COVID-19 pandemic, which has the potential to cause new health problems, is a complex issue that must be responded to with appropriate policies by the Government of Myanmar. Resolving inter-ethnic conflicts together with overcoming the COVID-19 pandemic is a major task of the Government of Myanmar. Equitable the disbursement of aid funds from the Myanmar government and public awareness to maintain health protocols are crucial to dealing with the conflict amid the COVID-19 pandemic. This study aims to see how the Myanmar government responds to the humanitarian and health crisis emergency in the COVID-19 pandemic. This research uses a qualitative method of case study with analytical descriptive. This research uses a conflict resolution management approach that must be completed by the Government of Myanmar.